Identification of cellulose-degrading bacteria isolated from shipworms in selected areas in Eastern Visayas - Agno, Alaniss Viveca F.; Mallonga, Zoe K. (2024)
Cellulose is a widely abundant biopolymer found in plant structures. Lignocellulose, derived from plant residues like wood, presents a substantial biomass resource for renewable energy due to its cost-effectiveness. Shipworm-associated bacteria have garnered interest due to the discovery of intracellular symbiotic bacteria within their gills capable of cellulose hydrolysis. This study aimed to identify cellulose- degrading bacteria acquired from shipworms in Eastern Visayas through qualitative and quantitative assessments. Qualitative assessment involved the visualization of cellulose degradation using insoluble powdered cellulose, while quantitative assessment employed a modified Dinitrosalicylic acid method. Results showed positive cellulose degradation among the 11 bacterial isolates studied. Furthermore, quantitative analysis revealed an increase in cellulase concentration by the fourth day of incubation, albeit accompanied by a large standard deviation (SD). Characterization of the isolates based on colony characteristics, gram-staining, and substrate tests classified them within the genus Teredinibacter. The capability of Teredinibacter sp. to hydrolyze cellulose highlights their potential use in industrial microbiology, specifically for the bioprocessing of lignocellulose waste in order to be used as bioethanol.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.